Introduction to Computer Vision: An End-to-End Guide for Beginners - Sharma, Kirti; Gupta, Chhaya (International Journal of Computer Sciences and Engineering, 2022)
Images are very easy to understand and remembered by humans. The human brain can understand if the image belongs to a dog or a cat by just having a look at it. Computer vision is one of the subjects in artificial intelligence that made it possible for a machine to visualize objects like a human brain. Although, the machine can visualize objects like human brain but still the path is so long to reach the accuracy of a human brain. The amount of data we collect today, which is subsequently utilised to train and improve computer vision, is one of the driving drivers behind its rise. Computer vision is the science by which various objects can be detected in fraction of time with the help of neural networks. Early computer vision investigations began in the 1950s, and by the 1970s, it was being used commercially to discern between typed and handwritten text. Today, computer vision applications have evolved tremendously. In this paper, a general introduction to computer vision is provided with an understanding of all the concepts of computer vision. A basic neural network is implemented from scratch for the same. The basic neural network developed achieves an accuracy of 89.13% when trained on Fashion MNIST dataset.